2017
DOI: 10.1097/01.aoa.0000527025.25005.7e
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Progression to Severe Disease in Women With Late Preterm Hypertensive Disorders of Pregnancy

Abstract: Introduction If hypertensive disorders of pregnancy are diagnosed before term, the benefits of immediate delivery need to be weighed against the neonatal consequences of preterm delivery. If we are able to predict which women are at high risk of progression to severe disease, they could be targeted for delivery and maternal complications might be reduced. In addition, this may prevent unnecessary preterm births in women at low risk. Material and methods We developed a prediction model using data from the HYPIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Ideally, more specific advice on restrictive intravenous fluid administration could be included in the Norwegian guidelines. By solely decreasing the blood pressure and not electively inducing labor, there is a risk of covering up a more serious disease with worse outcomes (23). In 1998, the advice was to pay close attention and to continuously review the situation, but no specific advice on the timing of delivery was given.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, more specific advice on restrictive intravenous fluid administration could be included in the Norwegian guidelines. By solely decreasing the blood pressure and not electively inducing labor, there is a risk of covering up a more serious disease with worse outcomes (23). In 1998, the advice was to pay close attention and to continuously review the situation, but no specific advice on the timing of delivery was given.…”
Section: Discussionmentioning
confidence: 99%
“…The 2009 HYPITAT I study (11) revealed that a conservative approach to treatment and elective delivery leads to a significantly higher risk of maternal morbidity compared with an approach with induction before gestational week 37. By solely decreasing the blood pressure and not electively inducing labor, there is a risk of covering up a more serious disease with worse outcomes (23). In 2012-2014, only two women died from preeclampsia and eclampsia in the UK, which is approximately one death per 1 000 000 pregnancies (7).…”
Section: Discussionmentioning
confidence: 99%